Assemblr EDU Augmented Reality Puzzle for Elementary Learning: Pengembangan Puzzle Augmented Reality Assemblr EDU untuk Sekolah Dasar - Age Larasati, Diyas; Binti Muhamad Hanafi, Nurfirdawati (Universitas Muhammadiyah Sidoarjo, 2026)
This study responds to the integration of digital technology in elementary education. General Background: Twenty-first-century learning requires interactive and student-centered instructional media supported by technology. Specific Background: In many elementary classrooms, learning media remain static, while puzzle-based learning and Augmented Reality (AR) platforms such as Assemblr EDU are often applied separately. Knowledge Gap: Research integrating puzzle-based problem-solving activities with AR technology into a single structured medium using Assemblr EDU at the elementary level remains limited. Aims: This study aims to develop and evaluate the feasibility of an Assemblr EDU–based augmented reality puzzle learning media using the ADDIE Research and Development model. Results: Expert validation showed material suitability (87%), visual design (83%), AR interaction (85%), and ease of use (82%), with an overall feasibility score of 84.25% categorized as appropriate to very appropriate. Student responses were highly positive in attractiveness (90%), usability (85%), conceptual support (88%), and thinking activation (87%). Novelty: The study integrates structured puzzle activities with AR visualization within one interactive instructional product. Implications: The developed media demonstrates pedagogical relevance and provides a viable technology-based alternative for elementary learning aligned with 21st-century education principles. Highlights• Achieved high validation scores across content, design, interaction, and usability criteria.• Generated strong learner approval in attractiveness, clarity, and cognitive activation aspects.• Combined structured game mechanics with three-dimensional visualization in one instructional product. KeywordsAugmented Reality; Assemblr EDU; Puzzle Based Learning; Elementary Education; Instructional Media Development